A INCLUSÃO DO DEFICIENTE VISUAL NOS ESTABELECIMENTOS ALIMENTÍCIOS DO MUNICÍPIO DE BETIM - LAGES, NAIARA CRISTINA; PEREIRA DE ALMEIDA, JONAS; MACHADO FERREIRA, ISABELA; RODRIGUES PEDRA MARQUES, JUSSARA; DA SILVA SALES, VIVIAN; GARABINI LAGES, CINTIA (Sinapse Múltipla, 2019)